Validism in the Elderly. Social Context and Functional Capacity - Mairovy Hernández Romero; Hilda María Delgado Acosta; Lourdes Elena Duany Badell; Belkis González Aguiar; Ismaray Sacerio González; Zenia Tamara Sánchez García (Revista Finlay)
Foundation: aging is a fact that affects the entire world population, and considerably, the most developed countries, in which life expectancy has been increasing as reflected in the United Nations report. Objective: to describe the social context and functional capacity in gerontos of clinic # 8 of Health Area I of the Cienfuegos municipality during the year 2022. Method: a descriptive cross-sectional study was carried out. A 30 % sample was randomly selected for a total of 131 elderly people. A structured interview was carried out, which included the general variables: age, sex, level of education, occupation, personal pathological history, support collaboration and to complete the social assessment, the Family Functioning Questionnaire was applied. Results: the age group of 60 to 65 years had the most prevalence, 45.5 % studied until they completed primary school, followed by those who completed secondary school with 29.0 %. Retirees were represented at 38.9 %, the main non-communicable diseases that prevailed were: high blood pressure, ischemic heart disease and type 2 diabetes mellitus, 40.4 % lived alone, 19.8 % had a caregiver, 14.5 % did not receive support and 9.9 % of the elderly who were in a probable state of social need. Conclusions: a well-nourished, loved, supported older adult, with all basic needs satisfied, as well as all associated diseases typical of this stage of life compensated, will have a better quality of life in any society.